Intertwining of localized (d) and delocalized (π) spins in magnetically frustrated two-dimensional metal-organic frameworks - Ugale, Ajay; Ninawe, Pranay; Jain, Anil; Sangole, Mayur; Mandal, Rimpa; Singh, Kirandeep; Ballav, Nirmalya (Inorganic Chemistry, 2024)
Two-dimensional metal-organic frameworks (2D MOFs) are emerging as a new class of multifunctional materials for diversified applications, although magnetic properties have not been widely explored. The metal ions and organic ligands in some of the 2D MOFs are arranged in the well-known Kagome lattice, leading to geometric spin frustration. Hence, such systems could be the potential candidates to exhibit an exotic quantum spin liquid (QSL) state, as was observed in Cu-3(HHTP)(2) (HHTP = hexahydroxytriphenylene), with no magnetic transition down to 38 mK. Hereto, we have investigated the spin intertwining in a bimetallic 2D MOF system, M-3(HHTP)(2) (M = Cu/Zn)(,) arising from the localized (d-electron) and delocalized (pi-electron) S = 1/2 spins from the Cu(II) ions and the HHTP radicals, respectively. The origin of the spin frustration (down to 5K) was critically examined by varying the metal composition in bimetallic systems, CuxZn3-x(HHTP)(2) (x = 1, 1.5, 2), containing both S = 1/2 and S = 0 spins. Additionally, to gain a deeper understanding, we studied the spin interaction in the pristine Zn-3(HHTP)(2) system containing only S = 0 Zn(II) ions. In view of the quantitative estimate of the localized and delocalized spins, the d-pi spin correlation appears essential in understanding the unusual magnetic and/or other physical properties of such hybrid organic-inorganic 2D crystalline solids

Influence of ionic radius on structural, optical and multiferroic properties of RMnO3 [R= Y, Er, Yb] hexamanganites - Inchara, D. R.; Singh, Kirandeep; Sangole, Mayur; Murari, M. S.; Daivajna, Mamatha D. (Physica B-Condensed Matter, 2025)
The crystalline samples of YMnO3, ErMnO3, and YbMnO3 were synthesized by a conventional solid-state reaction technique. The single-phase hexagonal structure with the P63cm space group was verified by X-ray diffraction (XRD) study. Morphological studies show that the grains are uniform and closely packed, and that the grain size increases as the ionic radii of the rare-earth ions decrease of rare earth ions and the samples are in the stoichiometry. From the Diffused Reflectance Spectroscopy study, narrow optical band gap is observed for all the samples. Magnetic phase transitions, corresponding to the antiferromagnetic ordering, were detected for all samples. The Neel temperature was found to increase with the decrease of the ionic radii of A site element in RMnO3 (Y, Er, and Yb) samples. Ferroelectric hysteresis loops at room temperature as a function of applied electric fields reveal the leaky behaviour. The dielectric constant and dielectric loss tangent variation across different frequencies are also explored for these samples. A summary and discussion of the structural, optical, magnetic and ferroelectric properties, underlying physical mechanisms, the role of the rare earth ions, and the complex interactions in hexagonal manganites, are presented in this paper. This work emphasizes how systematic variation of A-site ionic radii influences the multiferroic properties of RMnO3, gaining thorough insights into structure-property relationships that are essential to design multifunctional materials.
Keywords: Antiferromagnetic; ferroelectric; Multiferroics; Perovskites; Photovoltaic; Recombination centers